The evolution of 5GHz WLAN toward higher throughputs. - Simoens, S. (IEEE Wireless communications)
A standardization effort has started within the IEEE 802.11 working group to define the next generation of 802.11 wireless LANs. This article illustrates how throughput achieved above the MAC layer of 5 GHz WLANs can be increased from an existing 30 Mb/s maximum with 802.11a/g to rates exceeding 90 Mb/s. After a brief review of ongoing WLAN standardization activities, the support of a higher physical-layer bit rate by various standardized MAC protocols (802.11, 802.11e, and HIPERLAN/2) is discussed, showing the PHY and MAC layers must be considered jointly in order to achieve a significant throughput increase. Various physical layer techniques are compared in terms of performance and complexity. In particular, simulations show that by relying on MAC layers with good efficiency like 802.11e and HIPERLAN/2, a combination of space-time block coding with a possibility of channel bundling could bring a peak throughput increase from 30 to 90 Mb/s as well as a significant cell range increase.